Pulmonary Metastasis In Recurrent Myxoid Liposarcoma Despite Histological Grade -A CASE REPORT - H, Deepak.; Mark Franklin, Samuel; Balaji, V; R, Ganesh.; Karthickeyan, K. (Journal of Neonatal Surgery, 2025)
Background: Myxoid liposarcoma is an uncommon malignancy of adipocyte origin in soft tissue. Despite being characteristically low-grade, it has an uncharacteristic tendency for recurrence and distant metastasis, most frequently to the lung. A case of recurrent myxoid liposarcoma with swelling of the right leg and metastasis to the lung in a 60-year-old male is described here. Case Report: A 60-year-old male patient presented with a history of recurrent calf swelling of the right leg and multiple previous excisions (2005, 2010, 2014) presented with a new calf swelling. Imaging and biopsy revealed recurrent myxoid liposarcoma. PET-CT revealed local invasion and pulmonary metastasis. Chemotherapy with gemcitabine and docetaxel was initiated. Lifestyle counseling and a follow-up visit were advised. Conclusion: This case highlights the importance of Myxoid liposarcoma, though a low-grade sarcoma, is characterized by extensive local invasion and distant metastasis. Early treatment and appropriate systemic management are essential to manage recurrence and metastasis.